Antimicrobial effects of Melaleuca alternifolia (tea tree) essential oil against biofilm‐forming multidrug‐resistant cystic fibrosis‐associated Pseudomonas aeruginosa as a single agent and in combination with commonly nebulized antibiotics. (1st November 2021) - Haines, R.R.; Putsathit, P.; Tai, A.S.; Hammer, K.A.
Abstract: Broth microdilution assays were used to determine minimum inhibitory concentrations (MICs) and fractional inhibitory concentration indices (FICIs) of tea tree oil (TTO), tobramycin, colistin and aztreonam (ATM) against clinical cystic fibrosis‐associated Pseudomonas aeruginosa (CFPA) isolates ( n = 20). The minimum biofilm eradication concentration (MBEC) and fractional biofilm eradication concentration index (FBECI) were also determined using a similar microbroth dilution checkerboard assay, with biofilms formed using the MBEC device ® . TTO was effective at lower concentrations against multidrug‐resistant (MDR) CFPA isolates ( n = 3) in a biofilm compared to in a planktonic state (MBEC 18·7‐fold lower than MIC). CFPA within biofilm was less susceptible to ATM, colistin and tobramycin compared to planktonic cells (MBEC 6·3‐fold, 9·3‐fold, and 2·1‐fold higher than MIC respectively). All combinations of essential oil and antibiotic showed indifferent relationships (FICI 0·52–1·72) when tested against planktonic MDR CFPA isolates ( n = 5). Against CFPA isolates ( n = 3) in biofilm, combinations of TTO/aztreonam and TTO/colistin showed indifferent relationships (mean FBECI 0·85 and 0·60 respectively), whereas TTO/tobramycin showed a synergistic relationship (mean FBECI 0·42). The antibiofilm properties of TTO and the synergistic relationship seen between TTO and tobramycin against CFPA in vitro make inhaled TTO a promising candidate as a potential therapeutic agent. Abstract : Significance and Impact of the Study : Infection and colonization with Pseudomonas aeruginosa is generally regarded as unavoidable in the adult cystic fibrosis population, and is a major source of morbidity and mortality. The biofilm‐forming capacity of P. aeruginosa is a key feature that confers tolerance to otherwise effective antimicrobials. This study provides in vitro evidence that tea tree oil (TTO) has antibiofilm activity and indicates that TTO has a synergistic interaction with tobramycin against P. aeruginosa biofilms. Our data provide an important start in exploring the potential of TTO as an inhalational antimicrobial therapy for infections with drug‐resistant P. aeruginosa .